The Analysis of Operational Cash Flow, Debt Ratio, Rate of Assets Return on Company Performance: ANALISIS ARUS KAS OPERASIONAL, TINGKAT RASIO HUTANG DAN TINGKAT PENGEMBALIAN ASET TERHADAP KINERJA PERUSAHAAN - Malau, Melinda (Fundamental Management Journal, 2017)
The research purposed to analyze operating cash flow, leverage and return on asset to the company’s performance. The method used in this research is multiple regression analysis using Eviews 9. The samples used in this research are 242 which is the data of 121 manufacturing companies listed in Indonesia Stock Exchange from 2014-2015. The results show that operating cash flow and return on asset variables have a significant positive effect on the company’s performance, while leverage has a significant negative effect on the company’s performance. Total asset and age of the firm have a significant positive effect on the company’s performance.Keywords: operating cash flow; leverage; return on asset; company’s performance.